Influence of Corrosion and Scale Deposition on Thermal Processes of Silicate Pipe Coatings - Ibragimov, N.Yu. (Herald of Azerbaijan Engineering Academy, 2025)
The study of scale deposits on the inner surface of the glass coatings of pipes was carried out. Experimental studies have shown that during long-term operation, slight deposits of scale centers are observed on the surface of the glass coatings of pipes, while a strong layer of scale forms on the inner surfaces of metal pipes. The virtual absence of deposits in vitrified pipes is due to the increased cleanliness of the glass surface and its resistance to the aggressiveness of substances dissolved in sea water. This eliminates the formation of scale centers with glass so small that it is washed away by sea water. The vitrified pipes were subjected to a cleaning cloth and then washed with a 5-8% hydrochloric acid solution. After cleaning the surface of the glass coating, the pipes had the original appearance of glass